2009
DOI: 10.1007/s00441-009-0847-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential localization of α’ and β subunits of protein kinase CK2 during rat spermatogenesis

Abstract: Protein kinase CK2 is a serine/threonine kinase expressed in organisms from yeast to human and is composed of a catalytic subunit (alpha or alpha') and a regulatory subunit (beta) forming a holoenzyme with the possible subunit combinations alpha(2)beta(2), alpha'(2)beta(2), or alphaalpha'beta(2). This kinase has been shown to be involved in embryonic development and gametogenesis. We have studied the expression of the CK2alpha' and CK2beta subunits during the first wave of spermatogenesis and in adult testis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
5
1
Order By: Relevance
“…These findings are consistent with previous reports that CK2β protein is abundantly and broadly expressed in early spermatogenesis as shown by in situ hybridization and immunohistochemistry in mice. 34,35 However, our results are inconsistent with researches on rats, 43 which indicates that CK2β protein is located in both germ cells and Sertoli cells. This discrepancy may be caused by variations between species.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are consistent with previous reports that CK2β protein is abundantly and broadly expressed in early spermatogenesis as shown by in situ hybridization and immunohistochemistry in mice. 34,35 However, our results are inconsistent with researches on rats, 43 which indicates that CK2β protein is located in both germ cells and Sertoli cells. This discrepancy may be caused by variations between species.…”
Section: Discussioncontrasting
confidence: 99%
“…CK2α and CK2α′ expressions were detected in the amnion and choriodecidua at the three trimesters. This result was unexpected because the CK2α′ isoform was found predominantly in the brain and testis, unlike the CK2α isoform, which had low cell and organ specificities [ 28 ]. We found that the expression levels of the CK2 subunits were independent of the FM layers and labor conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic disruption of CK2 α ′ resulted in a change in the shape of the sperm head in mice during spermatogenesis and in male infertility (Xu et al , ; Escalier et al , ). Recently, it has been reported that the CK2 α ′ subunit showed differential localization during spermatogenesis and CK2 had a possible role at various stages, a process that involved proliferation, meiosis, apoptosis and differentiation (Alvarado‐Díaz et al , ). These reports suggest that CK2 activity or a CK2‐dependent pathway contributes to male infertility.…”
Section: Introductionmentioning
confidence: 99%